Petrological and Geochemical Characteristics of Al-rich Pelitic Granulites/Paragneiss from Thana, District-Bhilwara Rajasthan: Implication for Its Origin - Thomas, Harel; Bidolya, Jyoti; Soni, Aman; Batri, Rishabh (Earth and Planetary Science, 2022)
Al-rich pelitic granulites/paragneiss are frequently observed in the mediumto high-grade metamorphic rocks of Thana. It is dominantly composed of sillimanite-kyanite-garnet-biotite-plagioclase-k-feldspar and a subordinate amount of quartz. Garnet both xenoblastic as well as idioblastic is wrapped round by flaky minerals. These Al-rich pelitic granulites are the result of the metamorphism of pre-existing sedimentary rocks under medium to high grade P-T conditions and consist essentially of sillimanite-kyanite -staurolite-garnet-biotite bearing Al-rich pelitic granulites/paragneiss. The geochemical data reflect that Thana pelitic granulite is of S-type and peraluminous in nature. Geochemically, the protolith for these Al-rich pelitic granulites/paragneiss are shale or greywacke. Paper records the petrography, geochemical characters and a probable origin of these Al-rich pelitic granulites/paragneiss. ER